Impact of Manufacturing Flexibility on Business Performance: Malaysian’s Perspective - Tan, Kong Woun; Lim, Kong Teong (Gadjah Mada International Journal of Business, 2019)
This research aims to investigate the impact of manufacturing flexibility on business performance. The manufacturing flexibility dimensions are mix, new product, labor, machine, material handling, routing and volume flexibility. The measures for the business performance are product market performance, customer satisfaction and profitability. The impact of manufacturing flexibility on business performance has been tested using a cross sectional study employing survey methodology, conducted within five manufacturing industries in Malaysia. Data were obtained from 137 returned questionnaires, which were analyzed using correlational and regression analyses. The results of the correlation analyses indicated that the manufacturing flexibility dimensions were positively and highly correlated among themselves, thus suggesting that the dimensions were interdependent. Meanwhile, the findings of the regression analyses provided support for the idea that manufacturing flexibility has a positive and significant impact on business performance. In other words, manufacturing flexibility improves business performance. In conclusion, this empirical research provides insights and a better understanding about the relationship between manufacturing flexibility and business performance. This research allows researchers/practitioners to gain in-depth knowledge about the concept of manufacturing flexibility and its impacts.